Caries-preventing effect of a hydroxyapatite-toothpaste in adults: a 18-month double-blinded randomized clinical trial - Paszynska, Elzbieta; Pawinska, Malgorzata; Enax, Joachim; Meyer, Frederic; Schulze zur Wiesche, Erik; May, Theodor W.; Amaechi, Bennett T.; Limeback, Hardy; Hernik, Amadeusz; Otulakowska-Skrzynska, Justyna; Krahel, Anna; Kaminska, Inga; et al. (Frontiers in Public Health, 2023)
Background: Dental caries is a worldwide challenge for public health. The aim of this 18 months double-blinded, randomized, clinical trial was to compare the caries-preventing effect of a fluoride-free, hydroxyapatite toothpaste (test) and a toothpaste with sodium fluoride (1450 ppm fluoride; positive control) in adults. Methods: The primary endpoint was the percentage of subjects showing no increase in overall Decayed Missing Filled Surfaces (DMFS) index. The study was designed as non-inferiority trial. Non-inferiority was claimed if the upper limit of the exact one-sided 95% confidence interval for the difference of the primary endpoint DMFS between test and control toothpaste was less than the predefined margin of non-inferiority (Δ ≤ 20%). Results: In total, 189 adults were included in the intention-to-treat (ITT) analysis; 171 subjects finished the study per protocol (PP). According to the PP analysis, no increase in DMFS-index was observed in 89.3% subjects of the hydroxyapatite group and in 87.4% of the subjects of the fluoride group. The hydroxyapatite toothpaste was not statistically inferior to a fluoride toothpaste with regard to the primary endpoint. Conclusion: Hydroxyapatite was proven to be a safe and efficient anti-caries agent in oral care. Clinical Trials: NCT04756557